Distribution, behaviour, bioavailability and remediation of poly- and per-fluoroalkyl substances (PFAS) in solid biowastes and biowaste-treated soil. (October 2021) - Bolan, Nanthi; Sarkar, Binoy; Vithanage, Meththika; Singh, Gurwinder; Tsang, Daniel C.W.; Mukhopadhyay, Raj; Ramadass, Kavitha; Vinu, Ajayan; Sun, Yuqing; Ramanayaka, Sammani; Hoang, Son A.; Yan, Yubo; et al.
Graphical abstract: Highlights: Biowastes including composts and biosolids contribute PFAS input to the environment. PFAS input via biowastes reaches food chain through uptake by plants and soil biota. Source control measures help to prevent PFAS input through biowaste application. PFAS can be removed via phytoremediation and soil washing using surfactants. Bioremediation is not effective for the destruction of biowaste-derived PFAS. Abstract: Aqueous film-forming foam, used in firefighting, and biowastes, including biosolids, animal and poultry manures, and composts, provide a major source of poly- and perfluoroalkyl substances (PFAS) input to soil. Large amounts of biowastes are added to soil as a source of nutrients and carbon. They also are added as soil amendments to improve soil health and crop productivity. Plant uptake of PFAS through soil application of biowastes is a pathway for animal and human exposure to PFAS. The complexity of PFAS mixtures, and their chemical and thermal stability, make remediation of PFAS in both solid and aqueous matrices challenging. Remediation of PFAS in biowastes, as well as soils treated with these biowastes, can be achieved through preventing and decreasing the concentration of PFAS in biowaste sources (i.e., prevention through source control), mobilization of PFAS in contaminated soil and subsequent removal through leaching (i.e., soil washing) and plant uptake (i.e., phytoremediation), sorption of PFAS, thereby decreasing their mobility and bioavailability (i.e., immobilization), and complete removal through thermal and chemical oxidation (i.e., destruction). In this review, the distribution, bioavailability, and remediation of PFAS in soil receiving solid biowastes, which include biosolids, composts, and manure, are presented.